THE ESSENCE OF COMPARATIVE LEGAL SYSTEMS IN THE DEVELOPMENT OF LEGAL STUDIES - Abdul Rokhim (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2021)
: The breadth of the scope of the study of law can be seen from its discussion which includes the making of a rule, regulation or policy, practice and implementation of these rules, human rights, trade, economics, ownership, obligations, taxes, and ethics and rules in relations between countries (or other commonly known in international law), and many more. The broad scope of legal science is because this field of science (law) covers all aspects of human life and is needed in all sectors. Thus, there is no human activity that is not regulated in the study of legal science. Legal history has its own uniqueness, because in addition to informing about the stages of development of law or legal science in a country, legal history also has a focal point to discuss important events that factually occurred in the development of legal science. The history of law is a method and science which is a branch of historical science, which studies, analyzes, verifies, interprets, compiles arguments, and tends to draw certain conclusions about every fact, concept, rule, and rule relating to the law that has ever been in force. Both chronologically and systematically, as well as causes and effects and their touch with what is happening in the present, both as contained in literature, manuscripts, and even oral speech, especially the emphasis on the unique characteristics of these facts and norms, so that they can find symptoms, arguments, and legal developments in the past that can provide broad insight for those who study it, in interpreting and understanding the current law. With this approach, of course, the unique characteristics of facts and legal norms that occur in a society/country will be clearly recorded in the writings of legal scientists, this is nothing but an effort to compare law in the development of legal studies.